English Speakers in Montérégie Facing Increased Unemployment and Ongoing Economic Disparities as Compared to Francophones - Provincial Employment Roundtable (PERT) (2024)

Les Québécois d’expression anglaise de la Montérégie font face à un taux de chômage accru et à des disparités économiques persistantes par rapport aux francophones - Provincial Employment Roundtable (PERT) (2024)

Caractéristiques sociodémographiques des minorités visibles - Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Longueil.

Caractéristiques sociodémographiques des minorités visibles - MRC La Vallée-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC La Vallée-du-Richelieu.

Caractéristiques sociodémographiques des minorités visibles - MRC Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Roussillon.

Caractéristiques sociodémographiques des minorités visibles - MRC Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Vaudreuil-Soulanges.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Centre.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Est.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Ouest.

Socio-Demographic Characteristics of Visible Minorities in Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Longueil, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in MRC de La Vallée-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de La Vallée-du-Richelieu.

Socio-Demographic Characteristics of Visible Minorities in MRC de Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Roussillon.

Socio-Demographic Characteristics of Visible Minorities in MRC de Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Vaudreuil-Soulanges.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Centre.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Est.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Ouest.

RTS de la Montérégie-Centre - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Employment Profile of English Speakers in Montérégie - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Montérégie’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Montérégie, as well as preliminary recommendations to help improve their labour market outcomes.

Profil d’emploi des Québécois d’expression anglaise de la Montérégie - Provincial Employment Roundtable (PERT) (2024)
Le présent rapport vise à approfondir la compréhension de la situation de l’emploi dans les communautés d’expression anglaise de la Montérégie, qui représentent des minorités linguistiques dans la région. Il s’agit d’une collecte de données les plus actuelles et complètes sur le contexte démographique de ce groupe et sa réalité sur le marché du travail. Les sujets traités – travail, taux de chômage, revenu, niveau de scolarité – ont pour but de brosser un portrait d’ensemble de l’emploi et de l’employabilité des Québécois·e·s d’expression anglaise (QEA) dans la région. En plus du contexte démographique et du visage de la population active des communautés d’expression anglaise de la Montérégie, le présent rapport examine les principales caractéristiques du marché du travail et des secteurs où travaillent ces groupes. À la toute fin, on présente certains défis et enjeux de l’emploi dans ces communautés ainsi que des recommandations préliminaires en vue d’améliorer les débouchés.